Benefits and trade‐offs of replacing synthetic fertilizers by animal manures in crop production in China: A meta‐analysis. (26th October 2019) - Zhang, Xiaoying; Fang, Qunchao; Zhang, Tao; Ma, Wenqi; Velthof, Gerard L.; Hou, Yong; Oenema, Oene; Zhang, Fusuo
Abstract: Recycling of livestock manure to agricultural land may reduce the use of synthetic fertilizer and thereby enhance the sustainability of food production. However, the effects of substitution of fertilizer by manure on crop yield, nitrogen use efficiency (NUE), and emissions of ammonia (NH3 ), nitrous oxide (N2 O) and methane (CH4 ) as function of soil and manure properties, experimental duration and application strategies have not been quantified systematically and convincingly yet. Here, we present a meta‐analysis of these effects using results of 143 published studies in China. Results indicate that the partial substitution of synthetic fertilizers by manure significantly increased the yield by 6.6% and 3.3% for upland crop and paddy rice, respectively, but full substitution significantly decreased yields (by 9.6% and 4.1%). The response of crop yields to manure substitution varied with soil pH and experimental durations, with relatively large positive responses in acidic soils and long‐term experiments. NUE increased significantly at a moderate ratio (<40%) of substitution. NH3 emissions were significantly lower with full substitution (62%–77%), but not with partial substitution. Emissions of CH4 from paddy rice significantly increased with substitution ratio (SR), and varied by application rates and manure types, but N2 O emissions decreased. The SR did not significantly influence N2 O emissions from upland soils, and a relative scarcity of data on certain manure characteristic was found to hamper identification of the mechanisms. We derived overall mean N2 O emission factors (EF) of 0.56% and 0.17%, as well as NH3 EFs of 11.1% and 6.5% for the manure N applied to upland and paddy soils, respectively. Our study shows that partial substitution of fertilizer by manure can increase crop yields, and decrease emissions of NH3 and N2 O, but depending on site‐specific conditions. Manure addition to paddy rice soils is recommended only if abatement strategies for CH4 emissions are also implemented. Abstract : Agronomic and environmental performances of substituting chemical fertilizer by animal manure were systematically quantified by the meta‐analysis of field experiments across the main crop production regions of China. Partially substituting fertilizer by manure significantly increased crop yields, but full substitution decreased yields. The response of crop to manure substitution varied largely among soil pH, manure types and experimental duration. Ammonia emissions can be reduced, but methane emissions from paddy fields were significantly stimulated due to substitution of fertilizer by manure. The proper site‐specific methods of manure application are suggested to sustain food security with lower environmental costs.